Umeå SIMSAM Lab: A register-based research program connecting childhood with lifelong health and welfare - Gustafsson, Per; Ivarsson, Anneli; Lindgren, Urban; de Luna, Xavier; Nilsson, Karina (Umeå University, 2019)
The Umea ̊ SIMSAM Lab in a nutshell:

1) The Lab was established for interdisciplinary research from childhood into lifelong health and welfare. It provides individual-level data on an entire nation’s population, covering demography, socioeconomics and health, otherwise rarely accessible to the re- search community.

2) Initiated in 2008 and launched in 2014, the Lab hosts comprehensive prospectively collected individual-level data on all 14.9 million individuals in Sweden between 1960 and 2010, including intergenerational links and geographical coordinates. The foundation is data from national registers at Statistics Sweden, rich in demography and socioeconomics. Health data come from national registers such as the Medical Birth Register, the Patient Register, the Prescribed Drug Register and the Celiac Disease Register. Regionally data have been enriched by systematic and long-term initiatives involving data collection on weight/height, lifestyle habits, self-rated health, injuries etc. Each person has a unique serial number that allows linkage on individual level from all data sources.

3) The combination of longitudinal and individual-level demographic, socioeconomic and health data provides unprecedented research opportunities. In addition, social relations within family, workplace and neighbourhood can be depicted as intergenerational links, and geographical coordinates are available.

4) Researchers are welcomed to make contact for collaborative projects. Contact information and details on data access are also available on: [www.simsam.org.umu.se].

Purpose:

We aim:
(1) to increase knowledge of social and environmental factors that are of importance to health and welfare during childhood and life as it continues, e.g. regarding family changes, exchanges between generations and geographical mobility.
(2) to increase knowledge of several childhood diseases (and injuries) considering the contribution of the social and economic context
(3) i) monitor the health and lifestyle of children from foetal life to adolescence, and identify any changes over time; ii) perform aetiological studies to increase the understanding of child-health determinants from a family and neighbourhood perspective; and iii) evaluate the Salut programme with respect to any changes in lifestyle, health and educational outcomes in the short and long term.
(4) to develop modern statistical methods for microdata research, primarily in order to perform aetiological studies with a life course perspective, and to assess complex interventions.

Ett registerbaserat forskningsprogram som knyter samman barndom med livslång hälsa och välfärd.

SIMSAM Lab erbjuder en unik infrastruktur med prospektivt insamlade individnivå data om hela Sveriges befolkning 1960–2010, cirka 14.9 miljoner individer, inkluderande intergenerationella länkar och geografiska koordinater. Varje person har ett unikt serienummer som tillåter koppling på individnivå från alla datakällor. Grunden är nationella uppgifter från SCB (demografi, socioekonomi, skolgång, mm.) och Socialstyrelsen (sjukhusvistelse, föreskrivna läkemedel, graviditeten, den nyföddes hälsa, mm.). Detta har berikats med Västerbottens läns landstings befolkningsdata (självskattad hälsa, vikt & längd, levnadsvanor, skador, etc.

För mer information se den engelska katalogsidan: https://snd.gu.se/sv/catalogue/study/EXT0282
Umeå SIMSAM Lab: Ett registerbaserat forskningsprogram som knyter samman barndom med livslång hälsa och välfärd
Keywords: health; hälsa; census data; folkräkningsdata; demography; demografi; Socioeconomic Factors; Socioekonomiska faktorer; Child; Barn; Registries; Register; longitudinal research; longitudinell undersökning; national register; nationellt register; EDUCATION; UTBILDNING; SOCIAL STRATIFICATION AND GROUPINGS; SOCIAL STRATIFIERING OCH GRUPPERING; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Migration; Migration; Employment; Sysselsättning; Unemployment; Arbetslöshet; Children; Barn; Youth; Ungdomar; Social welfare policy; Välfärdspolitik; Compulsory and pre-school education; Obligatorisk utbildning och förskoleutbildning; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); ECONOMICS; EKONOMI; HEALTH; HÄLSA; Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; Higher and further education; Gymnasial och högre utbildning; General health and well-being; Allmän hälsa och välbefinnande; Health care services and policies; Hälso- och sjukvårdstjänster och -politik; Medication and treatment; Medicinering och behandlingar; Diet and nutrition; Kost och näring; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Wounds and injuries; Sår och skador; Language and linguistics; Språk och lingvistik; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Family life and marriage; Familjeliv och äktenskap; Gender and gender roles; Kön och könsroller; Minorities; Minoriteter; Social and occupational mobility; Social och yrkesmässig rörlighet; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Social conditions and indicators; Sociala förhållanden och indikatorer; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Censuses; Folkräkningar; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Labour and employment policy; Arbetsmarknads- och sysselsättningspolitik; Public health; Folkhälsa; Natural Sciences; Naturvetenskap; Medical and Health Sciences; Medicin och hälsovetenskap; Social Sciences; Samhällsvetenskap